2007
DOI: 10.1016/j.tet.2006.08.107
|View full text |Cite
|
Sign up to set email alerts
|

Use of 2-aminopurine as a fluorescent tool for characterizing antibiotic recognition of the bacterial rRNA A-site

Abstract: Spectroscopic and calorimetric techniques have been employed to characterize the impact of incorporation of the fluorescent base analog 2-aminopurine into the 1492 or 1493 position of an E. coli rRNA A-site model oligonucleotide, as well as the energetics and dynamics associated with recognition of this A-site model oligomer by aminoglycoside antibiotics. The results of these studies indicate that incorporation of 2AP into either the 1492 or 1493 position does not perturb the structure or stability of the host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 30 publications
2
38
0
Order By: Relevance
“…The fluorescence spectra were obtained using a spectrofluorimeter equipped with a quartz cuvette of 1 cm path length and a thermally controlled cell holder 32. The fluorescence emission (λem) spectra were recorded from 300 nm to 450 nm, with the path length for fluorescence excitation and emission of 5 mm, at an excitation wavelength (λex) of 280 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The fluorescence spectra were obtained using a spectrofluorimeter equipped with a quartz cuvette of 1 cm path length and a thermally controlled cell holder 32. The fluorescence emission (λem) spectra were recorded from 300 nm to 450 nm, with the path length for fluorescence excitation and emission of 5 mm, at an excitation wavelength (λex) of 280 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Using replica exchange MD (REMD) simulations, Sanbonmatsu et al [6] estimated relatively low (0.8 kcal/mol) energy barriers for flipping of adenines in a ribosomal A-site model, consistent with fast flipping (that work predicted experimental values in the 0.5–5 kcal/mol range). Similarly, fluorescence anisotropy measurements performed on oligonucleotide A-site models suggest that the adenines stackdestack on the nanosecond timescale, with rotational correlation times of 0.540.15 ns for A1492 [72] and 0.470.09 ns for A1493 [73]. However, NMR carbon spin relaxation and relaxation dispersion studies [74] suggested micro- to millisecond timescales for full-range flips of the A-site nucleotides, with the nanosecond timescale corresponding to just partial destacking of the adenines.…”
Section: Resultsmentioning
confidence: 92%
“…Crystallographic studies completed on ribosomal subunits or entire ribosomes in the presence of aminoglycosides provided near atomic resolution information on codon–anticodon interactions and the complex’s interaction with aminoglycosides (1618). These studies served as a springboard for the Pilch and Hermann groups to develop fluorescence-based methods to study the effect that aminoglycosides have on A-site dynamics (1922). Subsequent crystallographic studies by the Cate group on whole intact Escherichia coli ribosomes revealed that, in addition to the A-site, aminoglycosides bind helix 69 in 70S ribosomes, helping to explain how aminoglycosides inhibit ribosomal recycling (8).…”
Section: Introductionmentioning
confidence: 99%